The Seed Repair Response during Germination: Disclosing Correlations between DNA Repair, Antioxidant Response, and Chromatin Remodeling in Medicago truncatula - Pagano, Andrea; Araújo, Susana de Sousa; Macovei, Anca; Leonetti, Paola; Balestrazzi, Alma (Frontiers in Plant Science, 2017)
This work provides novel insights into the effects caused by the histone deacetylase inhibitor trichostatin A (TSA) during Medicago truncatula seed germination, with emphasis on the seed repair response. Seeds treated with H2O and TSA (10 microM and 20 microM) were collected during imbibition (8 h) and at the radicle protrusion phase. Biometric data showed delayed germination and impaired seedling growth in TSA-treated samples. Comet assay, performed on radicles at the protrusion phase and four-day old M. truncatula seedlings, revealed accumulation of DNA strand breaks upon exposure to TSA. Activation of DNA repair towards TSA-mediated genotoxic damage was evidenced by the up-regulation of MtOGG1(8-OXOGUANINE GLYCOSYLASE/LYASE) gene involved in the removal of oxidative DNA lesions, MtLIGIV(LIGASE IV) gene, a key determinant of seed quality, required for the rejoining of DNA double strand breaks and TDP(TYROSYL-DNA PHOSPHODIESTERASE) genes encoding the multipurpose DNA repair enzymes tyrosyl-DNA phosphodiesterases. Since radical scavenging can prevent DNA damage, the specific antioxidant activity (SAA) was measured by DPPH (1,1-diphenyl-2-picrylhydrazyl) and Folin-Ciocalteu reagent assays. Fluctuations of SAA were observed in TSA-treated seeds/seedlings concomitant with the up-regulation of antioxidant genes MtSOD(SUPEROXIDE DISMUTASE, MtAPX(ASCORBATE PEROXIDASE) and MtMT2(TYPE 2 METALLOTHIONEIN). Chromatin remodeling, required to facilitate the access of DNA repair enzymes at the damaged sites, is also part of the multifaceted seed repair response. To address this aspect, still poorly explored in plants, the MtTRRAP(TRANSFORMATION/TRANSACTIVATION DOMAIN-ASSOCIATED PROTEIN) gene was analysed. TRRAP is a transcriptional adaptor, so far characterised only in human cells where it is needed for the recruitment of histone acetyltransferase complexes to chromatin during DNA repair. The MtTRRAP gene and the predicted interacting partners MtHAM2 (HISTONE ACETYLTRANSFERASE OF THE MYST FAMILY) and MtADA2A (TRANSCRIPTIONAL ADAPTOR) showed tissue- and dose-dependent fluctuations in transcript levels. PCA (Principal Component Analysis) and correlation analyses suggest for a new putative link between DNA repair and chromatin remodeling that involves MtOGG1 and MtTRRAP genes, in the context of seed germination. Interesting correlations also connect DNA repair and chromatin remodeling with antioxidant players and proliferation markers.